Etika publikování – quo vadis? - Macková, Marie (Univerzita Pardubice, 2013)
The rate of growth in scientific publication increases every year. Ethical integrity is essential to writing and publication. Important ethical concerns to consider while writing a manuscript include etiquette, fraudulent publication, plagiarism, duplicate publication, authorship, and potential for conflict of interest. Strategies have been developed to prevent or detect ethical violations, and use of these strategies will enhance ethical integrity when preparing a manuscript for publication. This paper deals with ethical concerns of publishing.
Publishing ethics – quo vadis?
Keywords: ethics; publishing; plagiarism; duplicate publication; authorship